2023
DOI: 10.1038/s41467-023-40264-3
|View full text |Cite
|
Sign up to set email alerts
|

MenT nucleotidyltransferase toxins extend tRNA acceptor stems and can be inhibited by asymmetrical antitoxin binding

Xibing Xu,
Ben Usher,
Claude Gutierrez
et al.

Abstract: Mycobacterium tuberculosis, the bacterium responsible for human tuberculosis, has a genome encoding a remarkably high number of toxin-antitoxin systems of largely unknown function. We have recently shown that the M. tuberculosis genome encodes four of a widespread, MenAT family of nucleotidyltransferase toxin-antitoxin systems. In this study we characterize MenAT1, using tRNA sequencing to demonstrate MenT1 tRNA modification activity. MenT1 activity is blocked by MenA1, a short protein antitoxin unrelated to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…M. tuberculosis encodes four MenAT TA systems, comprised of a nucleotidyltransferase (NTase) toxin and a cognate antitoxin belonging to one of three different families (Dy et al, 2014;Xu et al, 2023;Cai et al, 2020). Although, in vivo, menAT2 was recently shown to be required for M. tuberculosis pathogenesis in guinea pigs (Gosain et al, 2022), only menAT1 and menAT3 were shown to act as bona fide TA systems in their native host M. tuberculosis (Xu et al, 2023;Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…M. tuberculosis encodes four MenAT TA systems, comprised of a nucleotidyltransferase (NTase) toxin and a cognate antitoxin belonging to one of three different families (Dy et al, 2014;Xu et al, 2023;Cai et al, 2020). Although, in vivo, menAT2 was recently shown to be required for M. tuberculosis pathogenesis in guinea pigs (Gosain et al, 2022), only menAT1 and menAT3 were shown to act as bona fide TA systems in their native host M. tuberculosis (Xu et al, 2023;Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…tuberculosis encodes four MenAT TA systems, comprised of a nucleotidyltransferase (NTase) toxin and a cognate antitoxin belonging to one of three different families (Dy et al, 2014;Xu et al, 2023;Cai et al, 2020). Although, in vivo, menAT2 was recently shown to be required for M. tuberculosis pathogenesis in guinea pigs (Gosain et al, 2022), only menAT1 and menAT3 were shown to act as bona fide TA systems in their native host M. tuberculosis (Xu et al, 2023;Cai et al, 2020). The MenA3 antitoxin inhibits MenT3 through phosphorylation of a serine residue in the catalytic site (Yu et al, 2020), whilst MenA1 forms an asymmetric heterotrimeric complex with two MenT1 protomers, suggesting a different mode of inhibition (Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations